Diamond and Carbon Composites and Nanocomposites - Aliofkhazraei, Mahmood (IntechOpen, 2016)
During the past few years, scientists have achieved significant successes in nanoscience and technology. Nanotechnology is a branch of science that deals with fine structures and materials with very small dimensions - less than 100 nm. The composite science and technology have also benefits from nanotechnology. This book collects new developments about diamond and carbon composites and nanocomposites and their use in manufacturing technology.